Metodologia para avaliação de subsistemas de coleta, tratamento e destinação de resíduos urbanos: estudo de caso da cidade de Juazeiro do Norte, Ceará - Alcantara, Wladson de Queiroz (2016)
This work proposes to design and implement a methodology to diagnose technical, economic, logistical and environmental of a collection system, transportation, disposal, treatment and energy productive use of solid waste in an urban area. The Municipal Solid Waste (MSW) are one of the sources of Greenhouse Gas emissions in the atmosphere and their malice has caused negative impacts, such as pollution of the sea, perpetuation dumpsites and discredit the generation of employment and income of organized recyclables collectors. Notably in the city of Juazeiro do Norte-Ce, the problems arising from poor disposal of MSW require rapid resolution of public agencies to determine the actors involved in the reverse logistics of recyclable MSW so that you can structure the city a trade chain for recycling materials sent to the city dump as meets the National Policy of Solid Waste (PNRS), generating jobs and income for the scavengers. The objective of this study is to propose a methodology of alternative collection systems, transportation, disposal, treatment and energy use of MSW, with emphasis on the first three subsystems to be validated by application to the case of the city of Juazeiro do Norte-Ce for sector of MSW. The methodology is qualitative and quantitative, using Systemic Analysis, Content Analysis and Pairing to describe the case of Juazeiro and present policies and actions, we have used the Facilities Location Problem Capacity building for development of alternative scenarios in determining the number of ecopoints and their zones of influence. The results show the trend of technological route of MSW in the city and three alternative scenarios the number of ecopoints to minimize the cost of operation and maintenance. It was concluded that the RESFE methodology is adhered to evaluate alternative systems of collection, transportation, disposal, treatment and energy use of MSW, pointing to the "Scenario C - Optimised 2" as indicated the city of Juazeiro do Norte-Ce, besides having guided the propositions policies and actions in the light of PNRS.